Analisis Deep Ecology Arne Naess terhadap Krisis Iklim dalam Buku Bumi yang Tak Dapat di Huni - Wilda Nur Rosyidah; Elma Desi Murohishoh; Siti Anisatul Mardhiah; Tri Utami Oktaviani (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
The climate crisis is no longer just a concern for environmental activists, but has evolved into a strategic threat affecting global stability. The climate crisis is now worsening into a serious threat to the sustainability of human life and the existing ecosystems on Earth. In his book, "The Uninhabitable Earth," Arne Naess provides deep insights thru the Deep Ecology approach, which emphasizes the intrinsic value of all forms of life. This study explores the relationship between the environment and cosmology and its impact on human policies and behavior toward nature. By analyzing the interaction between humans and the environment, we show that a paradigm shift toward a holistic understanding can offer sustainable solutions to this climate crisis. The impact of the climate crisis is highly complex and widespread, leading to unstable weather patterns. These unstable weather patterns threaten agriculture, food security, and also result in more frequent and severe natural disasters. We need to explore the root causes of the current climate crisis, the impacts that have already occurred and may come, and the efforts that can be made by individuals, communities, and the international community to address such challenges. This research strongly highlights the importance of collective consciousness and moral responsibility in protecting the planet, while also inviting readers to reflect on their position within the broader web of life. Thru this approach, it is hoped that synergy between human development and environmental sustainability can be achieved.